Mechanisms of cognitive behavioral therapy vs. supportive psychotherapy in body dysmorphic disorder: An exploratory mediation analysis. (February 2023) - Greenberg, Jennifer L.; Phillips, Katharine A.; Hoeppner, Susanne S.; Jacobson, Nicholas C.; Fang, Angela; Wilhelm, Sabine
Abstract: Body dysmorphic disorder (BDD) is common, severe, and often chronic. Cognitive behavioral therapy (CBT) is the first-line psychosocial treatment for BDD, with well-established efficacy. However, some patients do not improve with CBT, and little is known about how CBT confers its effects. Neurocognitive processes have been implicated in the etiology and maintenance of BDD and are targeted by CBT-BDD treatment components. Yet, the malleability of these factors in BDD, and their potential role in mediating symptom improvement, are not well understood. Understanding how treatment works could help optimize treatment outcomes. In this secondary data analysis of a randomized clinical trial of CBT vs. supportive psychotherapy (SPT) in BDD (n = 120), we examined whether treatment-related changes in detail processing (Rey-Osterrieth Complex Figure test), maladaptive appearance beliefs (Appearance Schemas Inventory-Revised), and emotion recognition (Emotion Recognition Task) mediated treatment outcome. All constructs improved over time and were associated with symptom improvement. CBT was associated with greater improvements in maladaptive beliefs than SPT. None of the variables examined mediated symptom improvement. Findings suggest that with successful treatment, individuals with BDD demonstrate reduced neurocognitive deficits (detail processing, emotion recognition, maladaptive beliefs) and that CBT is more likely than SPT to improve maladaptive appearance beliefs. More work is needed to understand mechanisms of change and thus maximize treatment outcomes. Highlights: Examined mediators of CBT vs supportive psychotherapy for body dysmorphic disorder. Both treatments improved neurocognitive functioning and maladaptive beliefs. CBT was more effective than SPT in improving maladaptive appearance beliefs. There were no significant mediators of symptom improvement. Abstract : ClinicalTrials.gov identifier: NCT01453439.